Creation of Synergies Through Mergers and Acquisitions - Kedia, Vasudha (2007)
Although Mergers and Acquisitions have seemingly high risks attached, they have been around for almost a century, and are an important tool in the strategic growth of a firm. There has been ample Empirical evidence on the creation and destruction of value through the M&A activity, which have showed diverse results. Drawing upon this framework the primary focus of this research is to study whether value was created or destroyed for the target and/or bidding firms and shareholders involved in an M&A activity.